Measuring the outcome of contact tracing. 1. A description of the patient and contact populations studied. Issue 3 (June 1978) - Satin, A; Mills, A
Abstract : A standard system for health workers to record and handle information on patients and contacts was introduced to five clinics. Information on all the patients interviewed during the first quarter of 1975 was collected and analysed. An analysis of the characteristics of these patients showed variation between the clinics. However, regardless of what was being measured, there were always differences between men and women. It was found that not all infected patients were interviewed about their contacts. Unless or until contact tracing includes all infected patients, the effect of contact tracing on the control of the sexually transmitted diseases will be of limited value and difficult to assess.